PERAN KANTOR PERTANAHAN DALAM PENYELESAIAN SENGKETA TANAH TERINDIKASI OVERLAPPING UNTUK MEWUJUDKAN KEPASTIAN HUKUM DI KABUPATEN SUKOHARJO - Pingky Ardiana Indriani; Susilowardani Susilowardani; Desi Syamsiah (Sekolah Tinggi Pariwisata Mataram, 2022)
Land plays an important role in human life. So important is land for humans that it creates a desire to control and own it. This sense of ownership has led to land disputes. The dispute that arises is the issuance of duplicate land rights (dual certificates) by the Land Office. This research is an empirical legal research with research data sources derived from primary data (interviews) and secondary data (library studies). The research results that have been collected are then analyzed qualitatively. Settlement of land disputes at the Sukoharjo Land Office is first resolved through mediation between the parties with the presence of a third party as a mediator, if in mediation no agreement is reached between the parties then the dispute process is continued through the courts. Land Office officials should be more careful and thorough, especially when measuring and mapping